The future of education related to SDG 16 (peace, ‎justice and strong institutions): A position paper - Kowkas, Sultan; Shayeb, Shaheen; Bransi, Narmeen (International Journal on Education Insight, 2022)
The spreading aspects of the seventeen sustainable development goals have been of concern to ‎researchers in education worldwide. These goals have shed the light and grasped the attention to ‎very crucial issues. The significance of these issues (the cores of each SDG) not only lie in their ‎importance but also in their connectedness and mutual influence among each other. Education, ‎being the highest peak of achievement in every society, and hence in the whole (small) world, is ‎directly affected by each SDG. That was the reason for considering the future of Education in sight ‎of one of the most effective sustainable goals, namely, peace, justice and strong institutions. The ‎current paper is a position paper that discusses the float of the sixteenth sustainable goal along the ‎future of Education. The researchers propose two statements: firstly, SDG 4 (Quality Education) ‎and SDG 16 possess a reciprocal interaction property (i.e. they have mutual impact ‎on each other). ‎Secondly, this cyclic process has to start by first accomplishing SDG 16‎‏.